If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(530 + -1(-2.5x + 1760)) = 5(x + -492) Reorder the terms: 2(530 + -1(1760 + -2.5x)) = 5(x + -492) 2(530 + (1760 * -1 + -2.5x * -1)) = 5(x + -492) 2(530 + (-1760 + 2.5x)) = 5(x + -492) Combine like terms: 530 + -1760 = -1230 2(-1230 + 2.5x) = 5(x + -492) (-1230 * 2 + 2.5x * 2) = 5(x + -492) (-2460 + 5x) = 5(x + -492) Reorder the terms: -2460 + 5x = 5(-492 + x) -2460 + 5x = (-492 * 5 + x * 5) -2460 + 5x = (-2460 + 5x) Add '2460' to each side of the equation. -2460 + 2460 + 5x = -2460 + 2460 + 5x Combine like terms: -2460 + 2460 = 0 0 + 5x = -2460 + 2460 + 5x 5x = -2460 + 2460 + 5x Combine like terms: -2460 + 2460 = 0 5x = 0 + 5x 5x = 5x Add '-5x' to each side of the equation. 5x + -5x = 5x + -5x Combine like terms: 5x + -5x = 0 0 = 5x + -5x Combine like terms: 5x + -5x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 7x-3+12x+12=180 | | 7y+18=2y-2 | | 6x-4y+8y= | | 2y-9y+3x-2x= | | 9+x=4x-15 | | 7x-1=9+5x | | 17+5m=-7(3m+5) | | 5*(9x+4)-5x+(2*9)=0 | | 40=-5k | | 5x+10x-13=-90-x | | 3(5x-1)-6x=x+5 | | -22h+x=84 | | -3(x+9)-45=7-58 | | (x+5)(x+1)=60 | | 12-b=18 | | 6(8x+1)=342 | | 3(9-2)+4(7-2)= | | 3h+7=5h | | 6x+15-5x=-8-10 | | 0.5x-8=3.9x-25 | | -106=-2(-3+7n) | | -3a^2=24 | | 10x+12=6x+32 | | 7w-14w=42 | | 12x^2+23x-4=-14 | | -2+b/4=-5 | | 2(5a-3)-9a+12=0 | | 1+v/21=2 | | 5+7x=11-7x | | 10+x+120-x+60=180 | | 5+5=4+4 | | 6n-6=138 |